Arquitectura para el fortalecimiento del turismo rural - páramos Las Domínguez y Pan de azúcar - Gutiérrez Salazar, Juan Camilo; Berrio Duque, Mauricio (Universidad Antonio Nariño, 2021)
This research was carried out with the intention of contributing to the tourism development of the Valle del Cauca, focusing on tourism in the village of Tenerife in the municipality of El Cerrito. Social, cultural and environmental aspects were necessarily addressed so as not to overlook none of the influencing factors in this territory in the moorland area of the Central Cordillera.